The impact of HIV and tuberculosis interventions on South African adult tuberculosis trends, 1990-2019: a mathematical modeling analysis. (September 2022) - Kubjane, Mmamapudi; Osman, Muhammad; Boulle, Andrew; Johnson, Leigh F.
Highlights: We developed a tuberculosis (TB) transmission dynamic model for South Africa. We quantified TB incidence and mortality attributable to HIV between 1990 and 2019. We estimated the impact of TB programmatic interventions on TB incidence between 1996 and 2019. A significant proportion of TB incidence and mortality was attributable to HIV. TB screening and antiretroviral therapy led to substantial TB incidence reductions. Abstract: Objectives: To quantify the South African adult tuberculosis (TB) incidence and mortality attributable to HIV between 1990 and 2019 and to estimate the reduction in TB incidence due to directly observed therapy, antiretroviral therapy (ART), isoniazid preventive therapy, increased TB screening, and Xpert MTB/RIF. Methods: We developed a dynamic TB transmission model for South Africa. A Bayesian approach was used to calibrate the model to South African-specific data sources. Counterfactual scenarios were simulated to estimate TB incidence and mortality attributable to HIV and the impact of interventions on TB incidence. Results: Between 1990 and 2019, 8.8 million (95% confidence interval [CI] 8.3-9.3 million) individuals developed TB, and 2.1 million (95% CI 2.0-2.2 million) died from TB. A total of 55% and 69% of TB cases and mortality were due to HIV, respectively. Overall, TB screening and ART substantially reduced TB incidence by 28.2% (95% CI 26.4-29.8%) and 20.0% (95% CI 19.2-20.7%), respectively, in 2019; other interventions had minor impacts. Conclusion: HIV has dramatically increased TB incidence and mortality in South Africa. The provision of ART and intensification of TB screening explained most recent declines in TB incidence.